THE ROLE OF RENEWABLE ENERGY IN ACHIEVING SUSTAINABLE ECONOMIC GROWTH IN UZBEKISTAN (International conference on multidisciplinary science, 2025)
This thesis examines the pivotal role of renewable energy in driving sustainable economic growth in Uzbekistan. As the country seeks to shift from a fossil fuel-dependent economy to a more diversified and environmentally responsible model, renewable energy presents a promising pathway. The study explores how solar, wind, and hydropower initiatives contribute to energy security, environmental protection, job creation, and rural development. It also highlights the challenges Uzbekistan faces, including outdated infrastructure, regulatory hurdles, and limited financing. Despite these barriers, recent government reforms and international partnerships suggest a growing commitment to clean energy. With continued investment and institutional support, renewable energy can become a cornerstone of Uzbekistan’s green transition.